Functional exercises improve quality of life of obese depressed women: a case report study - Barbieri, João Francisco; Picerno, Daniela; Tomazelli, Débora; Palamedi, Jamile Baptista; Guitte, Vanessa Érika; Ahmadi, Shirko (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Depression is characterized by abnormal affective manifestations. This pathology is more frequent among women and is aggravated with the overweight/obesity. Regular exercises have been shown to combat the manifestations of depression, as well as to increase active behavior and improve the morphology. Objectives: This study aimed to evaluate the effect of functional training on morphology, physical activity level and quality of life of obese women with depression. Methods: Four women with mean aged 32.5 ± 10.6 underwent 2 months of functional training, which performed twice a week, each session 1-hour training. Participants were evaluated in 3 times (T): T1) pre-test; T2) at the end of first month (mid-test); and T3) at the end of the second month (post-test). Results: We observed significant changes for the waist circumference variable, and presented a reduction in mid-test and post-test, in relation to the pre-test (p<0.05). No changes were observed for the variables weight and BMI. It was observed a significant increase in the level of physical activity, with the mid-test and post-test in relation to the pre-test (mid-test: p<0.05; post-test: p<0.01). All the indices evaluated by the SF-36 questionnaire showed improvement at mid-test and post-test relative to the pre-test (p<0.05). Conclusions: The present study suggests that engagement in functional training programs provides a significant improvement in aspects related to quality of life and depression, as well as an increase in the level of physical activity, even in the absence of weight reduction.